THE EFFECT OF PSYCHOLOGICAL FACTORS TOWARDS CONSUMER PURCHASE DECISION OF NETFLIX IN PANDEMIC ERA - Moralos Kalangi; S. L. H. V. Joyce Lapian; Fitty Valdi Arie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Successful companies influence consumer buying decisions to market their products effectively and maximize sales. The purpose of this study is to determine the effect of psychological factors towards consumer purchase decision of Netflix in pandemic era. This study uses a quantitative approach. Technique analysis using multiple linear regression. The results showed that perception, motivation, learning, attitude and confidence together or simultaneously have a significant effect on consumer purchasing decisions of Netflix users at the Faculty of Economics and Business Unsrat. Perception, learning and attitude partially has no significant effect on purchasing decisions of Netflix users at the Faculty of Economics and Business Unsrat. Motivation and confidence partially have a significant effect on purchasing decisions of Netflix users at the Faculty of Economics and Business Unsrat. Companies need to consider their perceptions, learnings, or attitudes to improve their purchasing decisions.   Keywords: perception, learning, attitude, motivation and confidence